2023
DOI: 10.1021/acscatal.2c06306
|View full text |Cite
|
Sign up to set email alerts
|

[4Fe–4S]-Mediated Proton-Coupled Electron Transfer Enables the Efficient Degradation of Chloroalkenes by Reductive Dehalogenases

Abstract: Reductive dehalogenases (RDases) are key enzymes involved in the degradation of organohalide compounds. Despite extensive experimental and computational studies, the catalytic mechanism of RDases remains unclear. We show here that the proximal [4Fe–4S]1+ cluster of the reductive dehalogenase PceA can mediate a proton-coupled electron transfer (PCET) process to quench the substrate radical. Such a [4Fe–4S]1+-mediated PCET process is enhanced by both exchange and super-exchange interactions. The participation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…The dispersion correction was considered using Grimme’s D3BJ method . Previous studies indicate that the entropy correction has less impact on the catalytic reaction of metalloenzymes, and the relative electronic energy profiles at the QM/MM level of theory were used to evaluate the hydrolysis step.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The dispersion correction was considered using Grimme’s D3BJ method . Previous studies indicate that the entropy correction has less impact on the catalytic reaction of metalloenzymes, and the relative electronic energy profiles at the QM/MM level of theory were used to evaluate the hydrolysis step.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In a recent study 35 by the Wang group, it is shown that the pK a value of a crucial tyrosine residue reduces significantly in the presence of H-bonding interactions with surrounding charged/ polar amino acids. In our study, for the Cld enzyme, we also found that Y118 forms strong interactions with W155 and the propionate side chain of heme, and therefore, we perceive that the pK a value of Y118 may also reduce in a similar way as found in the study of Wang et al Therefore, we have also computed pK a shift in the presence of W155 and a propionate side chain of heme.…”
Section: Feasibility For Deprotonation Of Y118 Through Pk a Calculationmentioning
confidence: 99%
“…[18][19][20] Understanding the mechanisms and factors influencing the photooxidation of organic matter via PCET is essential for developing strategies to control and optimize these processes. By harnessing the power of light and PCET, researchers aim to design innovative and sustainable solutions for environmental remediation and the degradation of organic pollutants, 21,22 with potential applications in various fields, such as organic synthesis, [23][24][25] and renewable energy conversion. 4 The goal of this work is to elaborate a qualitative ab initiobased picture of the PCET reaction mechanism and dynamics in a photoexcited pyrido [2,3-b]pyrazine complex with methanol (PrdPyr-MeOH, Fig.…”
Section: Introductionmentioning
confidence: 99%